Photograph of the Royal Canadian Mounted Police headquarters in Regina, Northwest Territories,Canada - Unattributed (Trinity College Dublin, the University of Dublin, 2020)
Photograph of the Royal Canadian Mounted Police headquarters in Regina, Northwest Territories. From Michael Davitt’s tour of Northwest Canada in 1891. Written on the back: ‘Mounted Police headquarters Regina (N.W.T.) near where [Louis David] Riel was hung. Carriages in foreground those in [which] my party were driven from Regina – city being about 2 miles distant (Saskatchewan)’.